2016
DOI: 10.1016/j.comcom.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and connectivity in highway vehicular networks: A case study in Madrid

Abstract: The performance of protocols and architectures for upcoming vehicular networks are commonly investigated by means of computer simulations, due to the excessive cost and complexity of large-scale experiments. Dependable and reproducible simulations are thus paramount to a proper evaluation of vehicular networking solutions. Yet, we lack today a reference dataset of vehicular mobility scenarios that are realistic, publicly available, heterogeneous, and that can be used for networking simulations straightaway. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Having analysed the location of the maximum F/C value from the sectional data it was found that it is mostly coming from the midway section. However, during the on-set stage the maximum value is on the inner (downstream) section and congestion spreads outwards, while during the recovery the outer (upstream) section is the most congested [14], [15]. These data show that the congestion on-set starts downstream and it travels backwards, while the recovery starts upstream and it moves forward.…”
Section: On-set Of Congestionmentioning
confidence: 75%
“…Having analysed the location of the maximum F/C value from the sectional data it was found that it is mostly coming from the midway section. However, during the on-set stage the maximum value is on the inner (downstream) section and congestion spreads outwards, while during the recovery the outer (upstream) section is the most congested [14], [15]. These data show that the congestion on-set starts downstream and it travels backwards, while the recovery starts upstream and it moves forward.…”
Section: On-set Of Congestionmentioning
confidence: 75%
“…• Using the discretization model, we devise accurate approximations for the conditional PGFL and the meta distribution of the SIR due to the hardcore point process. Furthermore, we illustrate that the hardcore process (and subsequently the discretization model) approximate well the meta distribution generated from synthetic motorway traces [4], [5], while the conventional PPP fails. • We show that introducing hardcore distance, while keeping the intensity of vehicles fixed, reduces the Coefficientof-Variation (CoV) of the meta distribution.…”
mentioning
confidence: 88%
“…The studies in [5], [6] [5]. In the validation of our models, we will drop 600 snapshots from the initial ten minutes of the simulation, in order to allow the first vehicles entering the roadway reach at the exit.…”
Section: Validating the Model With Synthetic Tracesmentioning
confidence: 99%
“…We will use a shifted-gamma approximation for the distribution of interference from L 2 . The moments of interference and subsequently the gamma parameters for L 2 , k, β, , do not depend on the link distance d as in (5) and (6). The outage…”
Section: Multi-lane Motorway Vanetsmentioning
confidence: 99%